Rule of a Reversed Optimum (Economic and Political Thought, 2013)
The author tries to answer the question about the mechanism of historicevents, which initially look unimportant but from the time perspective forma logic of some kind of optimum, which for the revolt initiators turns out tobe the reverse of their initial intentions. The author highlights a noticeableregularity, which he calls a ‘rule of a reversed optimum’: a characteristic featureof great social changes is that they disrupt the commonly accepted valuesbut in consequence the new ones do not have to create a higher level andoptimization of individual parts of the system does not go hand in hand withmaintaining the optimum for it as a whole. That is what the social mechanismof great breakthroughs consists in. Their essence is that they are mainlyconnected with great property redistribution from former owners to the newones. The beneficiaries feel satisfied even if from the macro-economic pointof view the effectiveness of the whole system deteriorates. Contrary to themoralistic interpretation of history, which suspects the existence of somekind of ‘historic keynote’ supposedly aimed at achieving higher and highersocial optimum, the real changes take place abruptly and rather disorderly,in accordance with a particular rule of a reversed optimum being a denial ofa macro-social optimum. The rule of a reversed optimum makes them playthe role of objects rather than initiators.